LncRNA GAS5 Competitively Combined With miR-21 Regulates PTEN and Influences EMT of Peritoneal Mesothelial Cells via Wnt/β-Catenin Signaling Pathway - Fan, Yi; Zhao, Xingxu; Ma, Jianfei; Yang, Lina (Frontiers in Physiology, 2021)
Abstract Objective:Epithelial-mesenchymal transition (EMT) is an important factor leading to PF in end-stage renal disease (ESRD) patients.The current research aimed to evaluate the effect of long non-coding RNA growth arrest-specific 5 (lncRNA GAS5) in human peritoneal mesothelial cells(HPMCs)EMT and explore the potential molecular mechanisms. Materials and Methods: HPMCs were cultured under control conditions or withhigh glucose (HG). The cells were then treated with lncRNA GAS5, lncRNA GAS5 siRNA, withor without miR-21 inhibitor and PTEN transfection. Expression of lncRNA GAS5, miR-21,α-SMA, Vimentin, E-cadherin, phosphatase and tensin homolog deleted on chromosome ten (PTEN)PTEN, Wnt3a, and β-catenin were measured by real time PCR and Western blotting.Bioinformatics analyses were used to test the specific binding sites between the 3’ UTR of the PTEN gene, miR-21, and lncRNA GAS5. Rescue experiments were performed to confirm the lncRNA GAS5/miR‑21/PTEN axis in HPMC EMT. Results: We found that HG-induced EMT decreased lncRNA GAS5 and that overexpression of lncRNA GAS5 can attenuate EMT in HPMCs. In addition, lncRNA GAS5 regulated HG-induced EMT through miR-21/PTEN. Cotransfection of miR‐21 inhibitors remarkably increased PTEN expression and attenuated EMT in lncRNA GAS5 knockdown HPMCs. Moreover, rescueexperiments showed that overexpression of PTEN attenuated the EMT effects of lncRNA GAS5 siRNA in HPMCs. We also confirmed that the Wnt/β-catenin pathway was stimulated in lncRNA GAS5/miR-21/PTEN-mediated EMT. Conclusions: Our research showed that lncRNA GAS5 competitively combined with miR-21 to regulate PTEN expression and influence EMT of HPMCs via the Wnt/β-catenin signaling pathway. This study provides novel evidence that lncRNA GAS5 may be a potential therapeutic target for HPMC EMT.